Pulmonary hypertension secondary to respiratory disease and/or hypoxia in dogs: Clinical features, diagnostic testing and survival. (September 2019) - Jaffey, J.A.; Wiggen, K.; Leach, S.B.; Masseau, I.; Girens, R.E.; Reinero, C.R.
Highlights: More than 80% of dogs with pulmonary hypertension (PH) from respiratory disease/hypoxia had obstructive airway lung disease. Overall median survival time for dogs with respiratory disease/hypoxia and PH was 276 days. Dogs with systolic pulmonary arterial pressure ≥47 mmHg had significantly shorter survival times. A cutoff of ≥47 mmHg for systolic pulmonary arterial pressure was a fair predictor of non-survival. Dogs administered phosphodiesterase-5 inhibitors were four times more likely to survive in the study period. Abstract: Pulmonary hypertension (PH) is associated with substantial morbidity and if untreated, mortality. The human classification of PH is based on pathological, hemodynamic characteristics, and therapeutic approaches. Despite being a leading cause of PH, little is known about dogs with respiratory disease and/or hypoxia (RD/H)-associated PH. Therefore, our objectives were to retrospectively describe clinical features, diagnostic evaluations, final diagnoses and identify prognostic variables in dogs with RD/H and PH. In 47 dogs identified with RD/H and PH, chronic airway obstructive disorders, bronchiectasis, bronchiolar disease, emphysema, pulmonary fibrosis, neoplasia and other parenchymal disorders were identified using thoracic radiography, computed tomography, fluoroscopy, tracheobronchoscopy, bronchoalveolar lavage, and histopathology. PH was diagnosed using transthoracic echocardiography. Overall median survival was 276.0 days (SE, 95% CI; 216, 0–699 days). Dogs with an estimated systolic pulmonary arterial pressure (sPAP) ≥47 mmHg ( n = 21; 9 days; 95% CI, 0–85 days) had significantly shorter survival times than those <47 mmHg ( n = 16; P = 0.001). Estimated sPAP at a cutoff of ≥47 mmHg was a fair predictor of non-survival with sensitivity of 0.78 (95% CI, 0.52–0.94) and specificity of 0.63 (95% CI, 0.38–0.84). Phosphodiesterase-5 (PDE5) inhibitor administration was the sole independent predictor of survival in a multivariable analysis (hazard ratio: 4.0, P = 0.02). Canine PH is present in a diverse spectrum of respiratory diseases, most commonly obstructive disorders. Similar to people, severity of PH is prognostic in dogs with RD/H and PDE5 inhibition could be a viable therapy to improve outcome.